ICU bed # 7 - Arevalo, Rica. ([Quezon City VideoFlick Productions], 2007)
ICU bed # 7 is a quiet, funny and moving family drama about an ailing father (Eddie Garcia) and how his two daughters (Angel Aquino and Irma Adlawan) are torn whether to end or prolong his life is one of the conflicts and highlights of ICU bed # 7
VCD
Executive producers Alessandra Beltran, Rica Arevalo, writer-director Rica Arevalo.
Eddie Garcia, Angel Aquino, Nonie Buencamino, Irma Adlawan, Happee Sy
Keywords: Feature films; Family--Drama.